A Inserção da Competência Informacional nos currículos dos cursos de Biblioteconomia no Brasil e de Informação e Documentação na Espanha - Mata, Marta Leandro da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Nowadays, scientific researches are focused on the social responsibility of the librarian in his/her action towards the information society. It is understood that the librarian's professional formation should include content that focus on his/her social role, particularly on issues relating to information literacy, as the librarian is appointed as responsible for promoting, developing and implementing such programs in educational institutions. The present research aimed to analyze how the information literacy and pedagogical training content have been covered in Library Science courses in Brazil and for Information and Documentation on Spain, being characterizing itself as an exploratory, documentary and comparative research, in which analysis of curriculum, educational plans and interviews with teachers who teach on the subject discipline are made. Thus, the analysis of the results has been performed both qualitatively and quantitatively. As a result, in Brazil, it was found that there are 10 disciplines of information literacy, seven that are mandatory and three are optional; the nomenclature used is informational competence. In Spain, four are optional and only one in basic training. There is a standardization on the use of the term information literacy or informational literacy. The content of most disciplines that approach the theme includes the concept, programs, places of learning and the educational role of the librarian, considering that few courses in Library Science have didactic disciplines or education that enable students to understand the educational system, its organizational form, its learning theories. In the Spanish context, not disciplines of education are offered. However, students have the option to get their higher education as an elective discipline in other courses. It is considered that some courses of Information Science and Information and Documentation have returned...

Atualmente, tem-se enfocado, no âmbito das pesquisas científicas, a responsabilidade social do bibliotecário em sua atuação frente à sociedade da informação. Nesse contexto, compreende-se que a formação desse profissional deve abarcar conteúdos que enfoquem o seu papel social, sobretudo no que concerne às questões referentes à Competência Informacional, dado que o bibliotecário tem sido apontado como o responsável por promover, implementar e desenvolver programas desta natureza nas instituições de ensino. A presente investigação teve como objetivo analisar como a Competência Informacional e os conteúdos de formação pedagógica têm sido abordados nos cursos Biblioteconomia no Brasil e de Informação e Documentação na Espanha, caracterizando-se como uma pesquisa de cunho exploratório, documental e comparativo, realizando-se a análise dos currículos, dos planos de ensino e de entrevistas com professores que ministram a disciplina acerca do tema. Deste modo, a análise dos resultados foi realizada tanto de forma qualitativa como quantitativa. Como resultados, no Brasil, constatou-se que há 10 disciplinas de Competência Informacional, sendo que sete são de caráter obrigatório e três são optativas; a nomenclatura mais utilizada é Competência Informacional. Na Espanha, quatro são optativas e uma de formação básica; há uma normatização quanto ao uso do termo alfabetização em informação ou alfabetização informacional. O conteúdo da maioria das disciplinas que abordam o tema inclui o conceito, os programas, os locais de aprendizagem e o papel educacional do bibliotecário, considerando-se que poucos cursos de Biblioteconomia possuem disciplinas de didática ou da área de educação que possibilitam aos alunos compreenderem o sistema de ensino, sua forma de organização, suas teorias de aprendizagem. No âmbito espanhol, não são oferecidas disciplinas da área de educação. Entretanto, os alunos...
Keywords: Competência em informação; Biblioteconomia – Ensino - Brasil; Biblioteconomia – Ensino - Espanha; Curriculos; Information literacy